Maternal effects on the fecundity and egg quality of the Patagonian stock of the Argentine Hake (Merluccius hubbsi) - Macchi, Gustavo Javier (2013)
Influence of age, size and condition of spawning females on fecundity and oocyte quality were analyzed for Merluccius hubbsi Patagonian stock. Samples of mature females were collected in the spawning area during two research surveys carried out in the main reproductive peak in January 2010 and 2011. Batch fecundity (BF) ranged between 40,500 and 2,550,000 hydrated oocytes, and was positively correlated with total length, gutted weight, age, hepatosomatic index (HSI) and the relative condition factor (Kn). Relative fecundity ranged between 85 and 1040 hydrated oocytes and showed significant positive relationships with gutted weight, HSI and Kn; however coefficient of determinations were rather low for all regressions. Dry weight of 100 hydrated oocytes resulted between 1.8 and 3.95 mg and was positively correlated with all variables analyzed, and with batch and relative fecundity. Multiple regression models constructed employing females morpho-physiological characteristics as variables, evidenced maternal influence on fecundity and weight of the eggs. Larger individuals showed better condition, mainly revealed by higher HSI, and hydrated oocytes with larger oil droplets. Moreover larger hake females showed higher feeding activity during the spawning season in comparison with young individuals.